The effect of macro variables on the Jakarta Islamic Index - Thoha Yahya (Faculty of Business & Economics, Universitas Islam Indonesia, 2020)
Purpose: In this study, efforts have been made to explore the relationship between macroeconomic variables and the Jakarta Islamic Index during the period 2015.1-2019.8.Methodology: the formulated model is a model to show the relationship. Long-term and short-term analysis using the classic assumption test and unit root test, co-integration test, and Granger causality test in the context of the ECM framework. For this purpose, macroeconomic variables are used as a measure of influence on the Jakarta Islamic IndexFindings: The results showed. Based on the analysis that has been done through cointegration and ECM tests, there is a long-term relationship between inflation variables, BI interest rates, foreign exchange rates, and the money supply with JII in 2015.1-2019.8. There is a short-term relationship between inflation variables, BI interest rates, foreign exchange rates, and the money supply with JII in 2015.1-2019.8.Originality/contributions: This is the first study using JII in Indonesia which was registered at the Islamic University of Indonesia in 2015.1-2019.8